Respuesta :
***(2x²+6x-8):(x+5)=2x-4
-2x²-10x
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
-4x-8
4x+20
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
12 ⇒ A. statement is true.
***When x=-5⇒2*(-5)²+6*(-5)-8=12⇒B. statement is true.
***2x²+6x-8 can also be written as (x+5)*(2x-4)+12 so (x+5) is a factor of 2x²+6x-8⇒C. statement is true.
***When x=5⇒2*5²+6*5-8=72 is not 12⇒D. statement is not true
***(2x²+6x-8):(x+5)=2x+16
-2x²+10x
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
16x-8
-16x+80
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
72⇒F. statement is not true
***E. statement is not true.
-2x²-10x
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
-4x-8
4x+20
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
12 ⇒ A. statement is true.
***When x=-5⇒2*(-5)²+6*(-5)-8=12⇒B. statement is true.
***2x²+6x-8 can also be written as (x+5)*(2x-4)+12 so (x+5) is a factor of 2x²+6x-8⇒C. statement is true.
***When x=5⇒2*5²+6*5-8=72 is not 12⇒D. statement is not true
***(2x²+6x-8):(x+5)=2x+16
-2x²+10x
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
16x-8
-16x+80
⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻⁻
72⇒F. statement is not true
***E. statement is not true.